Seditions, and confronting them in the light of Islamic thought - Mahdi Saleh, Yasein (Al-Adab Journal, 2019)
Sedition and how to deal with it Praise be to God, and peace, and peace be upon his slaves whom he chose. "I ask you the torment of hell from the torment of the grave, from the sedition of the living and the dead, and the yoke of U Hiv, and the yath of U Heev, and the Yith, the Yith, the Yith, and the Yith, and if it was before them, Let them ask God, who believe and know the liars. And the importance of the issue of the question of God Almighty to serve the believers: (and fear of sedition does not hurt those who wronged you in particular). Hudhayfah ibn al-Yaman said in his justification for his great interest in asking the Prophet (peace and blessings of Allaah be upon him) about sedition, saying: "People used to ask the Messenger of Allaah (peace and blessings of Allaah be upon him) and asked him about evil. To avoid conflict in our time, the difficulty of distinguishing it, and preventing it from being the most violent and lethal, the research came to meet the urgent need in the lives of modern Muslims. The second demand made it to show the rows of conflict and not one degree of magnitude, importance and inclusiveness, that is Sumer, this heat that Sumit, or. He is always ready to sit with God’s rope and commit his writing and Sunnah to him. So he is not good and told us that we may not do it. From him, there is no evil but warned. In conclusion, Hao Tu is a Titch of an overlapping state of overlapping, with Sumer, with Status. Their types and how we deal with them and words of progress in it. And we ask God to pay in his words, and dedication to work, and writing to the recipients of research.